Al-Tijarah Madiyyah and Ethical Review in a Transaction Based on the Perspective of Islamic Law - majid, abd; Mahsun, Mohamad; Ma'ani, Bahrul; Firdaus, Abdullah (AJIS: Academic Journal of Islamic Studies, 2023)
Al-tijÄrah MÄdiyyah, or what is referred to as the sale between fellow human beings in Islam, is limited by certain laws that are very detailed and vary according to the type of sale. The development of digital technology in business affects both online and offline transaction activities and creates new behaviors and violations based on Sharia law. Hence, the objective of this study is to delve further into the traditions and detrimental effects of each type, supplemented with descriptions of specific instances from prior studies. This study employs a library-based research model that relies on verbal information obtained from textual sources, primarily the Quran, Hadith, scholar viewpoints, and previous research. The researcher initiated an investigation into the verses of the Quran and the Hadith, thereafter adhering to the viewpoints of past scholars and uncovering recent instances of Sharia law transgressions based on prior studies on commercial transactions. This research provided additional references to the concept of Al-tijÄrah in Islam, which motivated other researchers to investigate specific trade cases and find solutions based on Islamic Sharia clauses. It also addressed the incomplete definitions of the type Al-TijÄrah in many previous studies. This research also serves as a preventative strategy to ensure that every Muslim does not compromise their spiritual well-being in pursuit of worldly advantages in every commercial transaction.